Portable Food Menu Directory Using Altera Devices - Chi, Choong Tian (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
The technology field is increased robustly nowadays. The development of technology helps to improving quality and our life style. All work to be done quickly, accurately and with minimal mistake. The major problem facing by the restaurant or store is when managing their food menu directory. There are many inconveniences causes like when doing correction or adding new item to the traditional food directory. To overcome this problem, a portable food menu directory with touch screen function is designed using Altera DE2-70 board and display the content of food menu by using liquid crystal display (LCD) Touch Panel. The contents of food menu are designed as a picture and stored in the Flash memory and then display on the LCD Touch Panel. As designed, there are three pages will be display on LCD Touch Panel where the first page is a welcome cover page, next is the contents of foods, drinks and price, lastly page is the display for the foods and drinks. While the 2x16 LCD display will display the foods name, drinks name, number of quantity and price according to the location of a touch detected within the LCD Touch Panel display area. The total price will display on the 2x16 LCD when detect the TOTAL button location on the LCD Touch Panel display area have been touched. The source code is designed using Verilog Hardware Description Language (HDL) processed using Quartus II design software tool. With this portable food menu directory, contents and price can be modifying easily compare to the traditional food menu directory.